El artículo XXI del GATT y la agresión: hacia una interpretación compatible con la unidad del orden jurídico internacional - Pezzano, Luciano (2021)
This article contends that the World Trade Organization (WTO) rules are affected by the gravity of aggression and the consequences of its prohibition on international law. In this regard, article XXI of the General Agreement on Tariffs and Trade (GATT), by enabling the adoption of measures necessary for the protection of the essential security interests of a State «in times of war», must be interpreted in the light of general provisions on aggression. This objective will necessarily lead us to consider whether the bodies of the WTO dispute settlement system (DSS) are competent to understand, in a situation where an act of aggression has been committed and in general terms, what implications —mainly legal, but also institutional and political in nature— the violation of the jus cogens has in a dispute before the DSS. To this end, this investigation explores the content and scope of GATT’s article XXI and its interpretation, in particular, of the meaning of the term «war» in subparagraph b, subsection iii, and then considers the implications of its possible application in the light of international rules on aggression and the jurisdiction of SSD bodies in this regard. The article assesses the alternatives that a panel might face in view of an invocation of article XXI by an aggressor State and, rejecting the possibility of an interpretation and application of the provision isolated of the rules on aggression, explores possible solutions to which the panel may enter, maintaining the balance between the efficacy of the system and the unity of the legal order.